Netralitas Pejabat Negara: Etis dan Yuridis Sikap Wakil Bupati Garut Dalam Menghadapi Ormas Keagamaan - Rabiah, Salwa; Afifa, Erina Nur; Rahman, Hafizh Aulia; Muttaqin, Sumayya; Khalila, Khalisa Putri; Khairiyah, Lina Husnul; R, Fathia Mahira; Andradit, Atthariq; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to examine the ethical and juridical aspects of the neutrality stance taken by the Vice Regent of Garut, Luthfianisa Putri Karlina, in response to the sweeping actions conducted by the Islamic Ummah Alliance (AUI) against eateries operating during the day in Ramadan 2025. The study analyzes the suitability of the Vice Regent's reprimand actions against the organization within the legal framework and principles of public official neutrality in Indonesia. Through a juridical-normative approach, the research identifies that despite the issuance of a Community Compliance Decree by Forkopimda and MUI of Garut Regency, the decree is merely advisory and lacks the binding legal force of a regional regulation. The findings show that the Vice Regent's actions in reprimanding the religious organization were carried out in accordance with the authority outlined in Garut Regent Regulation Number 202 A of 2009 and align with the principles of due process of law and interfaith tolerance values. The study highlights the importance of balancing the enforcement of religious norms and protecting citizens' rights to engage in economic activities, particularly in multicultural societies. This case underscores the dilemma faced by public officials in addressing demands from majority groups while upholding good governance principles. The research reveals that the Vice Regent's firmness in condemning intimidation strengthens the government's legitimacy as a protector of diversity and guarantor of social order and justice. The findings contribute to developing an ethical decision-making model for public officials facing socio-religious pressures in regional governance and enrich understanding of the boundaries of public officials' authority in maintaining neutrality, legal interests, and socio-religious dynamics.